Research on isolated-forwarding technology oriented polymorphic network - Aihua LIU; Hanguang LUO; Jianzhong WEN; Zhiguo ZHAN (Dianxin kexue, 2023)
The polymorphic network adopted the idea of “separation of network technology system and supporting environment”, and through innovative network development paradigms, various existing or future network technology systems dynamically load and run on a fully dimensional and definable network environment in the form of network polymorph.The “self-directed and self-sustainable development” of diversified network technology systems was realized in the same physical facility.Based on the study of polymorphic network architecture, the technology of mutual isolation between network polymorphs was mainly proposed in polymorphic forwarding processing, and in the current Ethernet physical facilities, the Ethernet physical layer technology was used to realize the hard isolation function of polymorphic network forwarding, so as to achieve the effect of physical isolation of polymorphic network in the same Ethernet interface and switching medium, then provided independent forwarding environment support for network polymorph.